1998
DOI: 10.2105/ajph.88.2.233
|View full text |Cite
|
Sign up to set email alerts
|

The preterm prediction study: the value of new vs standard risk factors in predicting early and all spontaneous preterm births. NICHD MFMU Network.

Abstract: OBJECTIVES: This study was undertaken to determine the relationship between fetal fibronectin, short cervix, bacterial vaginosis, other traditional risk factors, and spontaneous preterm birth. METHODS: From 1992 through 1994, 2929 women were screened at the gestational age 22 to 24 weeks. RESULTS: The odds ratios for spontaneous preterm birth were highest for fetal fibronectin, followed by a short cervix and history of preterm birth. These factors, as well as bacterial vaginosis, were more strongly associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
211
3
15

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 400 publications
(242 citation statements)
references
References 26 publications
10
211
3
15
Order By: Relevance
“…52 Women with more than 1 preterm birth are also more likely to have prior early (<32 weeks) preterm birth, to demonstrate clinical and ultrasound evidence of short cervix (sonographic length <25 mm, and Bishop score >3), and to have a positive fibronectin at 22-24 weeks. 53 A study of women with a prior preterm birth found that the likelihood of recurrent preterm delivery varied greatly, from less than 10% in women with a cervical length greater than 35 mm and a negative fibronectin at 22-24 weeks to more than 60% when the cervical length was less than 25 mm and the fibronectin test was positive at 22-24 weeks. 54…”
Section: Recurrent Vs Nonrecurrent Preterm Birthmentioning
confidence: 99%
“…52 Women with more than 1 preterm birth are also more likely to have prior early (<32 weeks) preterm birth, to demonstrate clinical and ultrasound evidence of short cervix (sonographic length <25 mm, and Bishop score >3), and to have a positive fibronectin at 22-24 weeks. 53 A study of women with a prior preterm birth found that the likelihood of recurrent preterm delivery varied greatly, from less than 10% in women with a cervical length greater than 35 mm and a negative fibronectin at 22-24 weeks to more than 60% when the cervical length was less than 25 mm and the fibronectin test was positive at 22-24 weeks. 54…”
Section: Recurrent Vs Nonrecurrent Preterm Birthmentioning
confidence: 99%
“…There is no evidence that existing prenatal strategies influence the probability that a woman will have her first preterm infant (21)(22)(23). For women with a previous preterm delivery, there is some evidence that the prenatal administration of 17-alpha-hydroxyprogesterone acetate (24,25) and antibiotics for the treatment of bacterial vaginosis (26)(27)(28)(29)(30)(31) may decrease the risk of a subsequent preterm delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Невиношування вагітності є найчастішим ускладненням гестаційного процесу в жінок із багатопліддям. Частота передчасних пологів при багатоплідді становить 54,3% порівняно з 12% при одноплідній вагітності [8,9]. Втрачені вагітності складають майже 17% від усіх бажа-них вагітностей, при цьому 75-80% викиднів трапляються на ранніх термінах і тенденція до зниження цих показників, на жаль, відсутня [2, 10,11].…”
unclassified
“…До них від-носиться плацентарна дисфункція, істміко-цервікальна недостатність, інфекційно-за-пальний процес, імунні реакції та вроджені чи набуті тромбофілії, екстрагенітальні за-хворювання, нейроендокринні порушення, більшість з яких супроводжуються гестаген-ною недостатністю, починаючи ще з етапу прегравідарної підготовки [5,8]. Найчастіше переривання вагітності відбувається при ен-докринних формах невиношування у терміні від 7-9 і до 12 тижнів.…”
unclassified
See 1 more Smart Citation